Oil Price Shocks and Cyclical Dynamics in an Asymmetric Monetary Union - Volker Clausen; Hans-Werner Wohltmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This paper analyzes the dynamic effects of anticipated and unanticipated oil price increases in a small two-country monetary union, which is simultaneously characterized by asymmetric wage adjustments and asymmetric interest rate sensitivities of private absorption. Common external oil price disturbances lead in this asymmetric macroeconomic setup to temporary divergences in output developments across the monetary union. In the case of anticipated oil price increases the relative cyclical position is reversed in the course of the adjustment process. Complete stabilization of the output variables throughout the overall adjustment process requires a restrictive monetary policy being time inconsistent from a quantitative but time consistent from a qualitative point of view. That means that the central bank credibly announces a future reduction in the growth rate of the nominal money stock but actually implements a reduction, which is less restrictive than the original announcement. – – Dieser Beitrag untersucht die dynamischen Effekte antizipierter und nicht-antizipierter Ölpreiserhöhungen in einer kleinen Währungsunion mit zwei Mitgliedsländern, die gleichzeitig durch asymmetrische Lohnanpassungsgleichungen und asymmetrische Zinsreagibilitäten der Güternachfrage gekennzeichnet sind. In dieser strukturell asymmetrischen Währungsunion führen gemeinsame externe Ölpreisschocks zu vorübergehenden konjunkturellen Divergenzen innerhalb der Währungsunion. Im Fall antizipierter Ölpreiserhöhungen kommt es im Verlauf des Anpassungsprozesses zu einer Umkehrung des Konjunkturgefälles innerhalb der Währungsunion. Die Stabilisierung der Outputentwicklungen innerhalb der Währungsunion ist über den gesamten Zeitraum grundsätzlich möglich, erfordert jedoch eine Ausgestaltung der Geldpolitik, die in qualitativer Hinsicht zeitkonsistent, aber in quantitativer Sicht zeitinkonsistent ist. Sie erfordert nämlich, dass die Zentralbank für den Zeitpunkt der antizipierten Ölpreiserhöhung eine Verringerung der Wachstumsrate der Geldmenge glaubwürdig ankündigt, letztendlich zum späteren Zeitpunkt der Ölpreiserhöhung eine etwas schwächere geldpolitische Reaktion implementiert.
Keywords: E63; F41; 330; EMU; international policy transmission; oil price shock; time inconsistency; monetary policy